Comments on the T-dual of the gravity dual of D5-branes on S-3 - Araujo, Thiago R. [UNESP]; Nastase, Horatiu [UNESP] (Springer, 2015)
We consider an abelian T-duality on a deformation of the gravitational solution of [1], which is the gravity dual of N-c D5-branes wrapping a three-cycle inside a manifold that admits a G(2) structure. Performing the T-duality we find N-c D4-branes wrapping a two-cycle with non-trivial antisymmetric fields in the NS-NS and RR sector. We study some aspects of its dual field theory and we compare with the original solution.
Keywords: D-branes; AdS-CFT Correspondence; String Duality